Financial Performance Analysis using the Value For Money Approach: Case Study at UPT Sentra Terpadu Inten Suweno - Hastuti Selmi Rahmah; Etty Gurendrawati; Tri Hesti Utaminingtyas (PT. BATARI EDU CALYA, 2025)
This study aims to find out how the financial performance of the Technical Implementation Unit (UPT) of the Inten Suweno Integrated Center by using a value for money approach consisting of elements of economy, efficiency, and effectiveness in the 2018-2022 fiscal year. The research method used in this study is a descriptive analysis that analyzes and describes the financial performance of the use of the budget in the service program implemented using budget realization data and performance achievements for the 2018-2022 fiscal year. The analysis unit of this research was carried out at the Suweno Integrated Center in Bogor. The data analysis technique used in this study is in the form of quantitative descriptive analysis techniques. The results of the study show that the financial performance of the Inten Suweno Integrated Center UPT for the service programs implemented during 2018-2022 is economically categorized as economical performance with an average economic value of 98.83% with an output achievement of >100%. In terms of efficiency, financial performance is categorized as very efficient performance with an average efficiency value of 272.86%. And in terms of effectiveness, effective performance is categorized as effective with an average effectiveness value of 99.54%. The results of the economic performance of the Inten Suweno Integrated Center UPT show the ability of the UPT to manage its finances well so that there is no waste of funds, efficiency performance shows excellent budget management ability so as to produce maximum output and exceed targets, and effectiveness performance shows good service quality so that it succeeds in achieving the service goals set previously.